2010 IEEE International Frequency Control Symposium 2010
DOI: 10.1109/freq.2010.5556280
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of SAW delay lines on c-plane AlN/sapphire at elevated temperatures

Abstract: Aluminum nitride (AlN) on sapphire is a promising substrate for SAW (surface acoustic wave) sensors operating at high temperatures and high frequencies. To get an experimental measure of the suitability and temperature stability of such devices, several samples of SAW delay lines were fabricated on 2" c-plane (0001) sapphire substrates with 1 µm c-plane AlN layer on top. Time-and frequency responses were recorded during annealing treatments at temperatures up to 850°C and the signals were analyzed afterwards.I. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…Post-analysis shows no degradation of the AlN surface. Unfortunately, no intermediate measurement was performed between 630 and 858°C which would have clarified the operating temperature limit [21]. Note however that these results are in perfect agreement with some previous studies about the limits of platinum IDTs estimated at 750 °C [22].…”
Section: Background and State Of The Artsupporting
confidence: 87%
“…Post-analysis shows no degradation of the AlN surface. Unfortunately, no intermediate measurement was performed between 630 and 858°C which would have clarified the operating temperature limit [21]. Note however that these results are in perfect agreement with some previous studies about the limits of platinum IDTs estimated at 750 °C [22].…”
Section: Background and State Of The Artsupporting
confidence: 87%
“…Thus, it is necessary to find alternatives to LGS for specific applications. Recent studies have shown that AlN/Sapphire is a promising piezoelectric structure for hightemperature SAW applications [7][8][9][10][11][12], even in the GHz-range [13][14]. However, the oxidation of AlN prohibits the use of this structure above 700°C in air [11].…”
Section: Introductionmentioning
confidence: 99%
“…By now, all SAW devices are fabricated on the stiff substrates instead of flexible's, suah as LiNbO 3 [2], Piezoelectric (PE) thin films on Si wafer [3,4], diamond [5], Al 2 O 3 [6] and so on. SAW on flexible substrate is cheaper and can be bent easily, which is fitted for portable microfluidic applications, such as wrist health-care monitor.…”
Section: Introductionmentioning
confidence: 99%